Protocol for xenotransplantation of human skin and streptozotocin diabetes induction in immunodeficient mice to study impaired wound healing - Zhuqing Li; Brandon Sumpio; Enya Wang; Mauricio Contreras; Ikram Mezghani; Georgios Theocharidis; Aristidis Veves (STAR Protocols, 2023)
Summary: Here, we present a protocol for the integration of human skin onto the backs of diabetic immunodeficient mice, providing a versatile in vivo model for mimicking and studying mechanisms involved in impaired cutaneous wound healing. This protocol includes instructions for the grafting of human skin, induction of diabetes using streptozotocin and wounding/post-wounding care of immunodeficient mice, as well as suggested downstream tissue analyses. This preclinical mouse model can be used to validate the efficacy of newly developed wound dressings.For complete details on the use and execution of this protocol, please refer to Theocharidis et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.